Incidental finding of cardiac hydatid cyst during autopsy - Nishant Purbey; Amit Patil; Shreekant Bharti; Keshav Chandra; Shashank Ranjan (University of São Paulo, 2024)
Hydatidosis or echinococcosis is an endemic parasitic disease caused by the ingestion of eggs of echinococcal species worldwide. In India, the annual incidence varies from 1 to 200 per one 100,000 hab., with the highest prevalence reported in the Indian states of Andhra Pradesh and Tamil Nadu. The dog is the definitive host, while humans, sheep, and cattle are intermediate hosts. The disease usually involves the liver and lungs, with the kidney and other organs rare involvement. Cardiac hydatidosis is still further rare, seen in 0.2% to 2% of the patients who remain asymptomatic until the development of its complications. Sudden deaths in cardiac echinococcosis are mostly attributed to cardiac arrhythmias, coronary artery diseases, valvular diseases, cardiomyopathies, pericarditis, and cardiac tamponade. We, herein, report a rare case of cardiac hydatid cyst incidentally found during the autopsy of a 26-year-old male who died due to electrical injuries. A single greyish-white cystic mass measuring 1.5cm X 1.2cm was detected on the left anterior ventricular wall 4 cm above the apex and was confirmed microscopically as a hydatid cyst. The cause of death was attributed to external injury.